'Involve me and I learn': an experiential teaching approach to improve dyspnea awareness in medical residents. Issue 1 (31st December 2022) - Decavèle, Maxens; Serresse, Laure; Gay, Frédérick; Nion, Nathalie; Lavault, Sophie; Freund, Yonathan; Niérat, Marie-Cécile; Steichen, Olivier; Demoule, Alexandre; Morélot-Panzini, Capucine; Similowski, Thomas
ABSTRACT: Background: Dyspnea is a frightening and debilitating experience. It attracts less attention than pain ('dyspnea invisibility'), possibly because of its non-universal nature. We tested the impact of self-induced experimental dyspnea on medical residents. Materials and Methods: During a teaching session following the principles of experiential learning, emergency medicine residents were taught about dyspnea theoretically, observed experimental dyspnea in their teacher, and personally experienced self-induced dyspnea. The corresponding psychophysiological reactions were described. Immediate and 1-year evaluations were conducted to assess course satisfaction (overall 0–20 grade) and the effect on the understanding of what dyspnea represents for patients. Results: Overall, 55 emergency medicine residents participated in the study (26 men, median age 26 years). They were moderately satisfied with previous dyspnea teaching (6 [5–7] on a 0–10 numerical rating scale [NRS]) and expressed a desire for an improvement in the teaching (8 [7–9]). Immediately after the course they reported improved understanding of patients' experience (7 [6–8]), which persisted at 1 year (8 [7–9], 28 respondents). Overall course grade was 17/20 [15–18], and there were significant correlations with experimental dyspnea ratings (intensity: r = 0.318 [0.001–0.576], p = 0.043; unpleasantness: r = 0.492 [0.208–0.699], p = 0.001). In multivariate analysis, the only factor independently associated with the overall course grade was 'experiential understanding' (the experimental dyspnea-related improvement in the understanding of dyspneic patients' experience). A separate similar experiment conducted in 50 respiratory medicine residents yielded identical results. Conclusions: This study suggests that, in advanced medical residents, the personal discovery of dyspnea can have a positive impact on the understanding of what dyspnea represents for patients. This could help fight dyspnea invisibility.